Calidad de suelos dedicados a la producción de arroz (oryza sativa l.) Bajo inundación en la parroquia Canuto, Chone, Manabí - Bolaños Rodríguez, Héctor Antonio (2019)
Currently, rice soils face an accelerated process of anthropogenic degradation as a result of intensive agriculture, which threatens to decrease their fertility and health. In this sense, it is essential to know the current situation of the soils dedicated to rice under local conditions, in order to identify potential problems and take corrective actions in time. Therefore, the main objective of the research was to evaluate the quality of soils dedicated to the production of rice under flood in the parish of La Canuto, Manabí, Ecuador by means of fertility indicators. The work was developed during the dry season of 2018 in rice areas of Canuto, for which a sample of 20 rice farms was selected and georeferenced, from which representative samples of soil were taken at a depth of 20 cm, which were sent to the laboratory for its respective physical and chemical analysis. The chemical variables analyzed were concentrations of macro and micronutrients, organic matter (OM), pH, cation exchange capacity (CEC) and electrical conductivity (EC). Among the physical variables analyzed were texture, apparent density, real density and percentage of porosity. Finally, with all the chemical and physical variables analyzed, soil quality was categorized according to the Harmonized World Soil Classification (HWSD). The results showed that the soils of the Canuto parish show adequate levels of macro and micronutrients for the production of rice, with the exception of OM, N and Zn and were deficient in most of the soils evaluated. The ratio of cations, the percentage of saturation of bases and the CEC were adequate for rice cultivation. The EC showed that the soils of Canuto do not present problems of salinity. The pH was slightly alkaline in all the evaluated soils, but they do not represent a major problem for rice production. The predominant texture in rice paddy soils were clayey and the porosity, apparent density and real levels showed ideal conditions for the radical development of rice cultivation. According to the Harmonized World Soil Classification (HWSD) and according to the physical and chemical variables evaluated, Canuto rice soils are classified as fertile soils without limitations for the production of rice under flood.